Metallocene implanted metalloporphyrin organic framework for highly selective CO2 electroreduction. (January 2020) - Xin, Zhifeng; Wang, Yi-Rong; Chen, Yifa; Li, Wen-Liang; Dong, Long-Zhang; Lan, Ya-Qian
Abstract: Metal organic frameworks (MOFs) with tunable porosity and metal sites have been considered as excellent candidates for electrochemical CO2 reduction reaction (CO2 RR). However, the poor electron conductivity and electron-donating capability of MOFs constrain the improvement of catalytic efficiency. Herein, we implant metallocene in MOFs through a facile chemical vapor deposition method and thus-obtained catalysts present excellent CO2 RR electrocatalysis performances. For instance, the FECO of CoCp2 @MOF-545-Co can be as high as 97% at −0.7 V. The high performances might be attributed to the strong binding-interaction between metallocene and metalloporphyrin that can largely reduce the adsorption energy of CO2 as revealed by density functional theory calculations. The introduction of metallocene can serve as electron donator and carrier to create continuous electron transfer channel in MOFs and provide strong binding-interaction with metalloporphyrin during CO2 RR process to enhance the CO2 RR activity. This method might shed light on development of highly-selective CO2 RR electrocatalysts. Graphical abstract: A facile chemical vapor deposition protocol is reported to introduce metallocene into MOFs to construct CO2 reduction reaction electrocatalysts with excellent performances and a strong binding-interaction mechanism is revealed by density functional theory calculations, which paves a new way for the development of highly selective CO2 RR electrocatalysts. Image 1 Highlights: MCp2 as an electron-rich system was successfully introduced into MOF-545-Co by a chemical vapor deposition strategy. Thus-obtained electrocatalyst can selectively convert CO2 to CO with a high FECO of 97% at -0.7 V. A strong binding-interaction between CO2 and Co-TCPP during CO2 RR process is revealed by DFT calculations.